Trophic niche changes associated with habitat fragmentation in a Neotropical bat species - Muñoz-Lazo, Fernando J. J. [UNESP]; Franco-Trecu, Valentina; Naya, Daniel E.; Martinelli, Luiz A.; Cruz-Neto, Ariovaldo P. [UNESP] (Wiley, 2019)
Habitat fragmentation could alter ecological traits including species trophic habits. Here, we used carbon and nitrogen stable isotope ratios to establish differences in isotopic niche width and food resource use between forest fragments and the continuous forest for the phyllostomid frugivorous bat Artibeus lituratus. Using mist nests, we captured bats from two forest fragments and two sites in continuous forest, and sampled from each individual captured three body tissues with contrasting turnover rates (skin, muscle, and liver). Samples were collected between February and March (austral summer) and between August and September (austral winter). In addition, in each sampling site and season we collected potential food resources (fruits and insects) consumed by our A. lituratus. Our findings indicate that A. lituratus had a predominantly omnivorous diet, with high consumption of insects during summer in forest fragments. The increasing consumption of insects in these fragments seems to have led to a wider isotopic niche, in relation to the continuous forest. Because A. lituratus is typically a seed disperser, changes in trophic habits in the forest fragments from frugivory to insectivory may diminish their role in forest regeneration. Abstract in Portuguese is available with online material.
Keywords: análise de isótopos estáveis; Brazilian Atlantic Forest; feeding habits; forest regeneration; hábitos alimentares; Mata Atlântica; morcegos filostomídeos; phyllostomid bat; regeneração florestal; stable isotope analysis